Computer Assisted Sperm Analysis: A Review - Agustinus; Cennikon Pakpahan (Indonesian Andrology and Biomedical Journal, 2020)
Background: A semen analysis exam is a routine check that is done to evaluate fertility. The World Health Organization (WHO) recommended a manual method to obtain objective and standardized values. However, sometimes some errors can be found with this method such as motility. Computer-Assisted Sperm Analysis offers a way to reduce inaccuracies that often occur with manual methods. Reviews: CASA systems consist of a microscope which connected into a camera to detect microscopic sperm suspension images and a computer installed with special software to extract desired information and produce the desired output. In the morphological examination, CASA can reduce the coefficient of variation (CV) which is around 4.8% compared to the manual examination but the time required is longer than manual. CASA can visualize and evaluate sperm kinematics. Various parameters such as mean path velocity (VAP), curved velocity (VCL), straight-line velocity (VSL), lateral head displacement amplitude (ALH), or beat cross frequency can be obtained, and this allows a detailed view into the behavior of individual sperm. The limitations affecting CASA's ability to provide accurate results for sperm concentration and percentages of motile or progressively motile spermatozoa. Summary: CASA has several advantages through its ability to calculate more detailed parameters, but a qualified operator must operate it because there is some potential for misinterpretation. The combination of The Manual and CASA is highly recommended for better results.